Intermediate financial theory - Danthine, Jean-Pierre (Elsevier, 2005)
This book is ideally suited to students wishing to gain a deeper understanding of the basic concepts of financial economics beyond those presented in a typical MBA program without having to deal with unnecessary mathematical details. The exposition is superb and enriching of intuition. The book, written by two of the professions leading experts, is unique. The article is contented the updated edition of classic textbook that fills a gap between MBA level texts and PHD level texts, focuses on clear explanations of key concepts and requires limited mathematical prerequisites, new structure emphasizing the distinction between the equilibrium and the arbitrage perspectives on valuation and pricing, as well as a new chapter on asset management for the long term investors.